A Comparison of Flower and Grass Strips for Augmentation of Beneficial Arthropods in Apple Orchards - Dong, Zhaoke; Xia, Mengjing; Li, Cheng; Mu, Baofeng; Zhang, Zhiyong (Frontiers in Sustainable Food Systems, 2021)
Sowing plants that provide food resources in orchards is a potential habitat management practice for enhancing biological control. Flowering plants (providing pollen and nectar) and grasses (providing alternative prey) can benefit natural enemies in orchards; however, little is known about their relative importance. We studied the effect of management practices (flower strips, grass strips, and spontaneous grass) on arthropod predators under organic apple management regimes in apple orchards in Beijing, China. Orchards located at two different sites were assessed for 3 years (2017–2019). The cover crops had a significant impact on the abundance and diversity of arthropod predators. The grass treatment consistently supported significantly greater densities of alternative prey resources for predators, and predators were more abundant in the grass than in the other treatments. The Shannon–Wiener diversity was significantly higher for the cover crop treatment than for the control. Community structure was somewhat similar between the grass and control, but it differed between the flower treatment and grass/control. Weak evidence for an increase in mobile predators (ladybirds and lacewings) in the orchard canopy was found. Ladybirds and lacewings were more abundant in the grass treatment than in the other treatments in 2019 only, while the aphid abundance in the grass treatment was lowest. The fact that grass strips promoted higher predator abundance and stronger aphid suppression in comparison to the flower strips suggests that providing alternative prey for predators has great biocontrol service potential. The selection of cover crops and necessary management for conserving natural enemies in orchards are discussed in this paper.